Influence of Energy and Duration of Laser Pulses on Stability of Dielectric Nanoparticles in Optical Trap - Quy, Ho Quang; Luu, Mai Van; Hai, Hoang Dinh (Communications in Physics, 2012)
In this article the gradient force of optical trap using two counter-propagating pulsed Gaussian beam and the Brownian motion in optical force field are investigated. The influence of the energy and duration time of optical pulsed Gaussian beams on satability of nano-particle in trap is simulated and discussed.